Vitamin D3–assisted chemo-photodynamic therapy of rhabdomyosarcoma cancer cells for effective treatment. (23rd October 2018) - Mahmood, R; Khurshid, A; Khan, J A; Rafi, M; Aalam, M; Salman, M; Ikram, M
Abstract: The combination of therapeutic drugs interestingly enhances treatment outcomes compared to single-agent modalities. Vitamin D3 (VD) in the presence of photodynamic drugs likewise affects the therapeutic results. A rhabdomyosarcoma (RD) cell line was cultured for the evaluation of each therapeutic agent, i.e. photodynamic therapy (PDT), chemotherapy (Chemo), and their combination with and without VD. Diode laser ( λ = 630 nm ± 1 nm) was used as an illumination source. The uptake time of the photosensitizer was optimized by means of spectrophotometric measurements. Administered drug responses were assessed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay. VD treatment for 24 h enhanced cellular death by 10%–30% when used as a neoadjuvant agent in chemotherapy (cisplatin (CDDP), doxorubicin (DOX), and methotrexate (MTX)), thereby exhibiting synergistic effects (CI < 1). RD culture pretreated with VD for 24 h showed encouraging results (% viability) when exposed to CDDP ( 50%), DOX ( 50%), and MTX ( 58%). Culture after treatment with VD + Chemo (CDDP, DOX, MTX) was followed by PDT, and more encouraging therapeutic outcomes ( 80%, 70%, and 76%, respectively) were observed compared to prior treatment evaluation. VD-Chemo or VD-chemo-PDT therapeutic modalities based on prior measured optimal parameters showed good anti-cancer effects. These results suggest that the proposed sequence of combinational therapeutic agents may further enhance the existing cancer-treatment protocol.